THE EFFECT OF TRAINING, MOTIVATION AND COMPENSATION ON EMPLOYEE EFFECTIVENESS THROUGH JOB SATISFACTION AT PORT OFFICES AND PORT AUTHORITIES CLASS III KIJANG - Rachman, Abd.; Wibisono, Chablullah; Khaddafi, Muammar; Titik, Diana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of training, motivation and compensation on the effectiveness of employees' work through job satisfaction. The method used in this research is a causal model survey method, data collection using a questionnaire and distributed to 120 respondents. Statistical data analysis using SEM-PLS (Structural Equation Modeling-Partial Least Square) and using path analysis to examine the pattern of relationships that reveal the influence of variables on other variables, both direct and indirect effects. The results in the study indicate that training directly has no significant effect on the effectiveness of employees' work with p-values of 0.587> 0.05,